Long-term consequences of estrogens administered in midlife on female cognitive aging - Daniel, Jill M. (Horm Behav, 2015)
Many of the biochemical, structural, and functional changes that occur as the female brain ages are influenced by changes in levels of estrogens. Administration of estrogens begun during a critical window near menopause is hypothesized to prevent or delay age-associated cognitive decline. However, due to potential health risks women often limit use of estrogen therapy to a few years to treat menopausal symptoms. The long-term consequences for the brain of short-term use of estrogens are unknown. Interestingly, there are preliminary data to suggest that short-term use of estrogens during the menopausal transition may afford long-term cognitive benefits to women as they age. Thus, there is the intriguing possibility that short-term estrogen therapy may provide lasting benefits to the brain and cognition. The focus of the current review is an examination of the long-term impact for cognition of midlife use of estrogens. We review data from our lab and others indicating that the ability of midlife estrogens to impact estrogen receptors in the hippocampus may contribute to its ability to exert lasting impacts on cognition in aging females.